Deliverance Of Self-Regard In Jane Austen's Pride And Prejudice Novel (1813): A Psychoanalytic Approach - Anggista, Ayu Fauziah Sofy Citra; , Dr. Phil. Dewi Candraningrum,S.Pd,.M.Ed; , Titis Setyabudi,S.S,.M. Hum (2013)
The problem of this study is to reveal how to deliverance of self-esteem in the main character. The purpose of this study is to analyze the main character in the novel Pride and Prejudice by using Psychoanalytic Approach. The study is a literary study, which can be categorized into a descriptive qualitative study. The object of this study is Pride and Prejudice novel. The data sources are primary and secondary data sources. The primary data source is the novel Pride and Prejudice book and the secondary data are related to the primary data that support the analysis such as some books of psychology and website related to the research. The method used for collecting data is library research and documentation. The technique of data analysis is descriptive analysis. Based on the analysis, the writer concludes that the problem faced by the major character is strived to go out of her condition, it causes the writer to use psychoanalytic perspective such as: Id, Ego, and Superego. By using this method, it is known how Elizabeth Bennet as the major character can solve her problem.